Academic self-concepts of Aboriginal and/or Torres Strait Islander children from the Longitudinal Study of Indigenous Children - Prehn, Jacob; Peacock, Huw; Guerzoni, Michael Andre (The Australian Journal of Indigenous Education, 2020)
Abstract Self-concept is recognised as useful in facilitating understanding of the development of resilience, academic achievement and social and emotional maturity in children. This framework is valuable for studying minorities such as Indigenous children, for who a positive self-concept is a means of bolstering resilience and mitigating the inherited structural disadvantages of colonisation. This paper aims to understand the academic self-concept of Indigenous children in Australia through analysis of univariate, bivariate and multivariate data of Indigenous children aged 9.5–11 years from the Longitudinal Study of Indigenous Children Wave's 7 K Cohort. Results show overall positive levels of Indigenous children's self-perception at school. Further, factors such as level of relative isolation, teacher perception, peer relationships, feedback from mother and contact with community leaders and Elders is positively associated with Indigenous children's schooling mathematic and reading self-concepts. Ensuring that Indigenous students are supported by community, peers and parents, immersed in their culture and are recognised and supported by their teachers can alleviate the undesirable effects that structural inequalities may have on their academic self-concept.